Effect of Antimicrobial Plants on Indigenous Microorganisms from Rumen Bos Taurus in The Fermentation Process - Meyuliana, Aulia; Astuti, Tri (Journal of Animal Nutrition and Production Science, 2023)
Indigenous microorganisms (IMO) are used in various agricultural activities. IMO used as a bioactivator for animal feed fermentation. IMO from bovine rumen B. taurus can be used as a bioactivator but it has contamination with pathogenic microorganisms. The antimicrobial plants tested to suppress the growth of pathogenic microorganisms during fermentation were Syzygium polyanthum, Cassia alata, Anredera cordifolia, and Piper betle. Antimicrobial plant fermented with rumen fluid. The results of IMO fermentation with antimicrobials were then analyzed for the microorganisms that grew in them and the display of the number of microorganisms growing. The results of the most growth of microorganisms are without antimicrobial treatment. The suppression of microbial growth on indigenous microorganism fermentation with antimicrobial plant C. alata obtained the highest yield, which was able to suppress up to 84% of microbial growth on NA medium.